(3CTYGQ eNJGQI ef OjhGf cTGLes - (3cTGLe , eMehO Hf GdMSjf Hf GdSfOj Hf TGgc, CHh GdaJM,J (B360 (3g` s
(3ChdgG (B:s
(3Qb KhH GdOLi hWGH GdghGA hJOdJ ddeZQH GdLhRGA s
(3BNQgG (B:s
(3dcfj de jcf dj ef ojSGYOfj hgG CfG eSYO ef cGf eMRhfG s
(3Vef eLehY s
(3GfXQ GdeNWhW eY eLehYI TYQjI ChdgG CQLhRI aj eYGfj eKdKGJ bWQHs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B43 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B159s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B30 s
Keywords: (3GdCOHs